Patients with 47, XXX karyotype who experienced premature ovarian failure (POF): two case reports. (5th July 2013) - Sugawara, Nobuo; Maeda, Machiko; Manome, Tomomi; Nagai, Rie; Araki, Yasuhisa
Abstract: Purpose: Pubertal onset and sexual development are usually normal in 47, XXX individuals; however, we report two cases of premature ovarian failure (POF) in infertile women with trisomy X. Methods: Chromosome analysis was conducted with G‐banding and fluorescence in situ hybridization using X‐ and Y‐bearing probe. Hormonal administration was primarily Kaufmann's treatment or long‐term estradiol treatment, followed by withdrawal bleeding from estrogen and progesterone. Results: Two patients with trisomy X, aged 31 (patient 1) and 27 years (patient 2), were diagnosed with POF due to hypergonadotropic hypogonadism. Their ovaries were small. Patient 1 had a FSH level of 44.6 mIU/ml and patient 2 had a FSH level of 74.6 mIU/ml. In patient 1, with Kaufmann's treatment, the FSH decreased to 13.5 mIU/ml; however, follicle growth did not occur following HMG stimulation. In patient 2, FSH did not decrease despite Kaufmann's treatment; therefore, she was given a GnRH agonist and her FSH level decreased to 7.1 mIU/ml. However, her ovaries never responded to HMG stimulation. Conclusion: We report on two patients with a 47, XXX karyotype who became infertile due to POF. We recommend that when a patient is diagnosed with trisomy X, the possibility of POF must be strongly considered.